(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
We present two cases of compound heterozygous state for hemoglobin (Hb) D and HbE who reported to the hospital for fever and incidentally found moderate microcytic hypochromic anemia. Later on they were investigated by capillary hemoglobin electrophoresis. Capillary Hb electrophoresis revealed compound heterozygous state for hemoglobin D and hemoglobin E. On family screening, father of one patient turned out to be HbD trait and mother as HbE trait. Due to unavailability of parents and siblings of other patient, family screening was not possible. Compound or double heterozygous state for HbD and HbE is rare. There are only six published reported cases of such double heterozygous state for HbD and HbE in Southeast Asia. Marriage between third degree relatives, which are more common among Muslims as well as inter caste marriages, common in some states of India have resulted into this compound heterozygous condition. Such double heterozygous case is clinically silent as compared to HbE/beta thalassemia or HbD/beta thalassemia.